Studies on Metal-Oxide Semiconductor ZnO as a Hydrogen Gas Sensor - C.S. Prajapati; P.P. Sahay (Журнал нано- та електронної фізики)
Metal-oxide semiconductor ZnO thin films were prepared on glass slides by spray pyrolysis technique at substrate temperature (410 ± 10) °C. Zn(NO3)26H2O was used as the precursor solution. The films thus prepared are undergone for structural and morphological studies using X-ray diffraction and scanning electron microscopy The films are found to be polycrystalline zinc oxide in nature, possessing hexagonal wurtzite crystal structure and nanocrystalline in grain size ~ 30-35 nm. The hydrogen sensing performance of the films has been investigated for various concentration of hydrogen in air at different operating temperatures in the range 200-400 °C. It is observed that the response is maximum (44.3 %) at the operating of temperature of 250 °C for 0.8 vol % concentration of hydrogen in air. A possible sensing mechanism for hydrogen has been proposed.